PROFILE OF UNDERSTANDING THE CONCEPT OF PYTHAGORAS THEOREM OF CLASS VIII STUDENTS IN TERMS OF COGNITIVE STYLE - Nita, Nita; Alfisyahra, Alfisyahra; Lefrida, Rita; Pathuddin, Pathuddi (Universitas Sembilanbelas November Kolaka, 2024)
Students' concept understanding needs to be profiled so that teachers can find out the level of description and understanding of students' mathematical concepts. The purpose of this study was to describe how the understanding of students of SMP Negeri Model Integrated Madani Palu in understanding the concept of pythagorean theorem in terms of cognitive style Field Independent (FI) and Field Dependent (FD). This type of research is descriptive with qualitative approach. The subjects in this study were students of class VIII Kihajar Dewantra SMP Negeri Model Integrated Madani Palu consisting of one student cognitive style Field Independent and one student cognitive style Field Dependent selected based on the results of the GEFT test. The instruments used in this study were GEFT test, concept understanding questions and interview guidelines. The results showed that students with Field Independent cognitive style can solve problems well based on indicators of concept understanding compared to students with Gield Dependent cognitive style. Based on these conditions, in the learning process the teacher should pay attention to the learning model used in learning activities.